Kebijakan Pemerintah Indonesia Bagi Stabilitas Perekonomian Pada Saat Covid-19 - Akbarti Na'ima; Imam Mukhlis; Sugeng Hadi Utomo (Transformasi: Journal of Economics and Business Management, 2022)
At the end of 2019 towards the beginning of 2020, the world was shaken by a virus known as Coronavirus Disease (covid-19). The Covid-19 pandemic began in the city of Wuhan, Hubei Province, China and then spread to 200 countries, impacting various sectors of the global economy. Fighting this virus requires strategies and policies to regulate the economy. This article describes the Indonesian Government's Policy for Preeconomic Stability During Covid-19. The research method used is descriptive qualitative in the form of literature studies or what is known as review literature. The results of this study show that although various policies carried out by the Indonesian government are appropriate, in their implementation, further steps are still needed to maintain the stability of the Indonesian economy.